Perbandingan Metode Latihan Bagian Dan Global Terhadap Keterampilan Lay Up Shoot - Andolin Putra; Windo Wiria Dinata; Endang Sepdanius; Hanif badri (JURNAL STAMINA, 2022)
The problem in this research is the lack of lay up shoot skills. This study aims to determine the effect of the section training method and the global training method on the lay up shoot skills in this study, the training method using sectional and global training with various training programs. This research is a quasi-experimental type. This research was conducted from February to March 2021 and was carried out on February 23, 2021 to March 31, 2021. The population in this study were students who participated in basketball extracurriculars with 25 members. The sample of this study was 20 people, sampling using purposive sampling technique. This research was conducted for 5 weeks (16 meetings), 3 meetings in 1 week of practice. Data analysis using t-test. The results of data processing are tcount training methods (9.49) > ttable (1.83) and tcount global training methods (6.53) > (1.83) and there is an increase in the results of the ability between pre-test and post-test, This means that the section training method and the global training method have an influence on the lay up shoot ability. The application of the section training method and the global training method has an effect on improving dribbling skills. And the part practice method is better for lay up shoot skills than the global training method